Standaarde vir die interhospitaalvervoer van siek neonate - M.E. Muller; A.G.W. Nolte; J.C. Roux (AOSIS, 1989)
The transport o f ill neonates between hospitals and/or health care centres, plays an important role in the mortality rate o f these seriously ill neonates. It is therefore important that the ill neonate is transported under optimal conditions. A lack o f standards in this regard hampers the evaluation o f the quality o f inter hospital transport o f ill neonates. The purpose o f this study is to formulate valid standards fo r the transport o f seriously ill neonates between hospitals (and/or other health care institutions) to form the basis fo r the evaluation o f the quality o f this service. Factors that need to be considered in the transport o f ill neonates include the ambulance, equipment and stock, the transport personnel and communication. These factors were systematically explored and described and standards were formulated accordingly.